Concurrent validity of the short-form Family Impact Scale (FIS-8) in 4-year-old US children - W. M. Thomson; L. A. Foster Page; S. M. Levy; M. A. Keels; A. T. Hara; M. Fontana (BMC Pediatrics, 2022)
Abstract Background US data on the validity and reliability of the short-form Family Impact Scale (FIS-8; a scale for measuring the impact of a child’s oral condition on his/her family) are lacking. Methods Cross-sectional analysis of data on four-year-old US children taking part in a multi-center cohort study. For child-caregiver dyads recruited at child age 12 months, the impact of the child’s oral condition on the family was assessed at age 48 months using the FIS-8, with a subsample of 422 caregivers (from 686 who were approached). Internal consistency reliability was assessed using Cronbach’s α, with concurrent validity assessed against a global family impact item (“How much are your family’s daily lives affected by your child’s teeth, lips, jaws or mouth?”) and a global oral health item (“How would you describe the health of your child’s teeth and mouth?”). Results Cronbach’s alpha was 0.83. Although gradients in mean scores across ordinal response categories of the global family impact item were inconsistent, there were marked, consistent gradients across the ordinal categories of the global item on the child’s oral health, with scores highest for those rating their child’s oral health as ‘Poor’. Conclusions While the findings provide some evidence for the utility of the FIS in a US child sample, the study’s replication in samples of preschoolers with greater disease experience would be useful.